Ultra-fast single-sequence magnetic resonance imaging (MRI) for lower back pain: diagnostic performance of a deep learning T2-Dixon pprotocol - Diallo, T. D.; Wiedemann, S.; Berkarda, Z.; Strecker, R.; Nickel, D.; Bamberg, F.; Rau, A.; Mayrhofer, Thomas; Russe, M. F.; Weiss, J. (Clinical radiology, 2025)
Background - Conventional magnetic resonance imaging (MRI) protocols for lower back pain require multiple sequences and long acquisition times, challenging healthcare systems amid rising demand for lumbar spine imaging. - AIM - To assess the diagnostic performance of an abbreviated, deep learning-accelerated sagittal T2w Dixon single sequence protocol (Protocolabb-DL) versus the standard lumbar spine MRI protocol (Protocolstd). - MATERIALS AND METHODS - In this prospective, single-centre study, 30 patients (mean age: 48 ± 18.5 years; 67% female) with lower back pain (LBP) underwent a single MRI examination using both Protocolstd (sagittal T1w and T2w turbo spin-echo sequences) and Protocolabb-DL. A senior radiologist (15 years experience) established the diagnostic reference standard using Protocolstd. Two independent readers (10 and 5 years’ experience) evaluated the images at a segmental level for degenerative pathologies, including Modic changes, disc pathology, facet arthropathy, neuroforaminal stenosis, and Schmorl nodes. Diagnostic performance, confidence, interprotocol, and interobserver agreements were analysed. - RESULTS - Protocolabb-DL reduced acquisition time by 80% at 1.5 Tesla (1:33 vs 7:43 minutes) and 84% at 3 Tesla (1:26 vs 8:43 minutes). Diagnostic performance was high, with sensitivities up to 100% [95% CI, 90.7-100.0] for Modic changes and 94.7% [95% CI, 87.1-98.5] for disc pathology, and specificities up to 100% [95% CI, 97.8-100.0] for Schmorl nodes. Diagnostic confidence was comparable between protocols (P > 0.05). Interprotocol agreement was excellent (κ: 0.84-1.00), and interobserver agreement for Protocolabb-DL was substantial to excellent (κ: 0.67-0.93). - CONCLUSION - Protocolabb-DL provides diagnostic performance comparable to Protocolstd for degenerative lumbar spine pathologies while reducing acquisition time by up to 84%.
Online verfügbar: 11. Juni 2025, Artikelversion: 8. Juli 2025
Gesehen am 20.08.2025